Laparoscopic hepatectomy is safe and effective for the management of patients with colorectal cancer liver metastases in a population-based analysis in Ontario, Canada. A retrospective cohort study. (November 2020) - Griffiths, Christopher D.; Xu, Keying; Wang, Julian; McKechnie, Tyler; Gafni, Amiram; Parpia, Sameer; Ruo, Leyo; Serrano, Pablo E.
Abstract: Background: Laparoscopic hepatectomy (LH) has been deemed safe, and, in the case of minor hepatectomy, the standard of care. Short-, long-term outcomes and costs of LH compared with open hepatectomy (OH) in patients with colorectal cancer liver metastases have not been well described at the population level. Materials and methods: Patients diagnosed with colorectal cancer undergoing hepatectomy were included in this population-based retrospective cohort study from 2006- to 2014. Postoperative complications (per Clavien-Dindo) and survival were analyzed using a linear mixed model and Cox-Proportional hazards model respectively. Costs of surgery and the 90-day postoperative period were considered in 2018 Canadian dollars and compared from the perspective of a third-party payer. Results: Over a median follow-up of 56 months, 95% confidence interval (CI): 51 to 68), there were 2991 hepatectomies (OH: 2551 (85%) and LH: 440 (15%)). LH compared to OH was more common for patients >70 years-old (30% vs. 22%, p = 0.004) and for minor hepatectomy (52% vs. 32%, p < 0.001) respectively. By multivariable analyses, OH was associated with similar 90-day mortality (Odds Ratio (OR) 1.05, 95% CI: 0.56–1.97), and overall survival (Hazard Ratio (HR) 1.08, 95% CI: 0.90–1.29), but higher rates of major postoperative complications (OR 1.34, 95% CI: 1.03–1.76), higher cost (median difference $6, 163, 95% CI: $3229 to $9096), and longer length of hospital stay (LOS) (mean difference 3.04 days, 95% CI: 2.7 to 3.91). Conclusion: LH was associated with lower postoperative complications, shorter LOS, which translated into lower costs to the healthcare system, without differences in postoperative mortality and survival. Highlights: This study supports increased uptake of laparoscopic hepatectomy in colorectal liver metastases. Laparoscopic versus open hepatectomy for colorectal liver metastases is associated with lower post-operative complications. Length of hospital stay is lower following laparoscopic hepatectomy, leading to decreased healthcare costs. Long term oncological outcomes are similar between laparoscopic and open hepatectomy for colorectal liver metastases.